2016
DOI: 10.1002/jcp.25316
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of Acute Lung Injury and Acute Respiratory Distress Syndrome

Abstract: The acute respiratory distress syndrome (ARDS), a severe form of acute lung injury (ALI), is a very common condition associated with critically ill patients, which causes substantial morbidity and mortality worldwide. Despite decades of research, effective therapeutic strategies for clinical ALI/ARDS are not available. In recent years, microRNAs (miRNAs), small non-coding molecules have emerged as a major area of biomedical research as they post-transcriptionally regulate gene expression in diverse biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 103 publications
3
99
0
Order By: Relevance
“…Fluid-based miRNA (serum, saliva, sputum, cerebrospinal fluid, plasma, whole blood, and urine) profiling could provide invaluable information for studies where the disease is not derived from only one type of cell or a specific type of cell. This possibility has opened doors for non-invasive diagnostic techniques in various disease states [49], [50], [51], [52], [53]. Hence miRNAs are considered good therapeutic targets in cancer and cardiovascular disease [54], [55], [56].…”
Section: Introductionmentioning
confidence: 99%
“…Fluid-based miRNA (serum, saliva, sputum, cerebrospinal fluid, plasma, whole blood, and urine) profiling could provide invaluable information for studies where the disease is not derived from only one type of cell or a specific type of cell. This possibility has opened doors for non-invasive diagnostic techniques in various disease states [49], [50], [51], [52], [53]. Hence miRNAs are considered good therapeutic targets in cancer and cardiovascular disease [54], [55], [56].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are important regulatory RNAs, which mainly function in repressing gene expression at the post-transcriptional level by binding to the 3′-UTR of target mRNAs through base pairing12. However, some researchers found out that miRNAs may also positively regulate target mRNAs3. Substantial evidence indicated that miRNA dysregulation is related to a number of human diseases, such as cancer45.…”
mentioning
confidence: 99%
“…Growing evidence indicates that dysregulation of miRNAs is closely associated with the pathogenesis of diseases including lung diseases [8].…”
Section: Introductionmentioning
confidence: 99%